Personalization and Visual Representation through Learning Analytics: A Meaningful Approach to Guide Self-Directed Learners - Thiyagarajan, Gomathi; S. , Prasanna (International Journal of Psychosocial Rehabilitation, 2020)
Due to technological advancement and global needs, educators are challenged with creating professionals who can exceptionally apply skill and competence in a changing world. In order to accomplish this, an educator must come up with a structure of self-directed learning techniques. This technique subsequently should enhance the student’s capabilities and provide a platform to self-evaluate their performance and proficiency without compromising their learning frequency. The field of learning analytics has significantly matured in tracing learners’ data from their digital footprint and providing valuable insights for improving the teaching-learning process. The researchers of this study aim to identify how learning analytics can be used as a tool for personalizing learning and what information an analytics dashboard can provide self-directed learners to scale up key competencies and skills.